National companies or foreign affiliates: Whose contribution to growth is greater? - Alice H. Amsden (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
National firms fulfill functions that foreign affiliates are less likely to undertake. For this reason, there is a growth/efficiency justification for government programs designed to support and promote national companies (public and private) as opposed to, and in competition with, opening the doors to MNEs.
Keywords: 330